2014
DOI: 10.1038/ijos.2014.22
|View full text |Cite
|
Sign up to set email alerts
|

Anti-proteolytic capacity and bonding durability of proanthocyanidin-biomodified demineralized dentin matrix

Abstract: Our previous studies showed that biomodification of demineralized dentin collagen with proanthocyanidin (PA) for a clinically practical duration improves the mechanical properties of the dentin matrix and the immediate resin–dentin bond strength. The present study sought to evaluate the ability of PA biomodification to reduce collagenase-induced biodegradation of demineralized dentin matrix and dentin/adhesive interfaces in a clinically relevant manner. The effects of collagenolytic and gelatinolytic activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
37
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 35 publications
0
37
0
3
Order By: Relevance
“…Proanthocyanidin from grape seed extract is a natural safe compound and works as well as glutaraldehyde (27). Proanthocyanidin extract stabilizes and increases the density of type-I collagen network (26), which improves the dentin mechanical properties and decreases the swelling ratio that may indicate a matrix resistance against enzymatic degradation (11,26). The results of the present study did not show a statistically difference between glutaraldehyde and proanthocyanidin extract at 24 h for all adhesives studied.…”
Section: Discussionmentioning
confidence: 37%
See 1 more Smart Citation
“…Proanthocyanidin from grape seed extract is a natural safe compound and works as well as glutaraldehyde (27). Proanthocyanidin extract stabilizes and increases the density of type-I collagen network (26), which improves the dentin mechanical properties and decreases the swelling ratio that may indicate a matrix resistance against enzymatic degradation (11,26). The results of the present study did not show a statistically difference between glutaraldehyde and proanthocyanidin extract at 24 h for all adhesives studied.…”
Section: Discussionmentioning
confidence: 37%
“…Glutaraldehyde is a synthetic aldehyde collagen cross-linking agent that decreases the rate of collagen degradation (26). However, it presents high cytotoxicity (8), which limited their clinical use.…”
Section: Discussionmentioning
confidence: 99%
“…19 For MMPs, cross-linkage of the catalytic sites of these enzymes and inhibition of other non-collagenous proteins that activate these enzymes also have been hypothesized. 20,21 Possibly, the combined cross-linking and anti-collagenolytic effects of PAs are responsible for preventing degradation of dentin collagen within the hybrid layer. 8 Results of the failure analysis by chi-square test, showed that a highly significant difference existed in between Groups 1 & 2 (p <0.0001).…”
Section: Discussionmentioning
confidence: 99%
“…Advantages of acid etching include high maneuverability, low cost, and non‐toxity 27 . However, studies on acid‐processed dentin have focused generally on dental acid corrosion materials rather than altering the characteristics of dentin for application as possible bone substitute material for clinical application 28–30 . Thus, parameters of acid etching and concrete physiochemical properties of treated dentin tissue remain to be explored.…”
mentioning
confidence: 99%